Pemanfaatan Kartu Jaminan Kesehatan Nasional (JKN) Dalam Meningkatkan Efektivitas Pelayanan Kesehatan Pada Puskesmas Menggamat - Maghfirah, Nurul; Duana, Maiza; Fitriani, Fitriani; Nabela, Danvil; Yarmaliza, Yarmaliza (An Idea Health Journal, 2025)
The Government always strives to improve the quality of public health services nationally, and one of these efforts is using social security. Utilizing health services using National Health Insurance can make it easier for people to seek treatment at no cost. With this national health insurance, people can enjoy the same service facilities and increase the effectiveness of health services at the Menggamat Community Health Center. Therefore, Community Health Centers are required to constantly make efforts and be committed to meeting the standards and regulations made by the Government. This research aims to determine what factors influence the use of the National Health Insurance Card (JKN) in increasing the effectiveness of health services at the Menggamat Community Health Center. This research is quantitative with a cross-sectional approach, conducted in January 2024 with 105 respondents using a purposive sampling technique. The data was analyzed using the Chi-Square test. There is no significant relationship between the level of education and utilization of National Health Insurance (JKN) with a p-value = 0.631 > 0.05 OR value of 1.375 (CI = 0373-5.069), there is a significant relationship between the level of knowledge and utilization of JKN with a p-value = 0.023 < 0.05 OR value of 2.531 (CI = 1.126-5.687) then there is a relationship between people's perception of seeking medical treatment from a healer/shaman and the use of JKN with a p-value = 0.002 < 0.05 OR value of 0.265 (CI = 0.113-0618). Services at the Menggamat Community Health Center can be said to be effective based on several criteria for measuring effectiveness; however, public awareness in carrying out health checks at the Menggamat Community Health Center is still lacking based on the perception of the community who still seek treatment from healers/shamans.